The seismicity of central and north-east Himalayan region - Susheel KUMAR; Nitin SHARMA (Contributions to Geophysics and Geodesy, 2019)
The Himalayan range extends upto 2400 km arc from Indus river valley in the west to Brahmaputra river valley in the east of India. Due to distinct geological structures of Himalayan seismic belt, seismicity in Himalaya is inhomogeneous. The inhomogeneity in seismicity is responsible for a number of seismic gaps in the Himalayan seismic belt. Thus Iin the present study, we proposed the study of spatial and temporal evolution of seismicity in entire central and north-east Himalayan region by using Gutenberg-Richter relationship. A detailed study on the behavior of natural seismicity in and around the seismic gap regions is carried out. The study region is segmented in four meridional regions (A) 80 °E to 83.5 °E, (B) 83.5 °E to 87.5 °E, (C) 87.5 °E to 90 °E and (D) 90 °E to 98 °E along with a fixed latitude belt. The homogeneous catalogue with 3 ≤ Mb ≤ 6.5 is used for the spatial and temporal analysis of seismicity in terms of b-value. It is find out that pockets of lower b-values are coinciding over and around stress accumulated regions. The observed low b-value before occurrence of the Nepal earthquake of 25th April, 2015 supports the argument of impending occurrence of moderate to large magnitude earthquake in Sikkim and north-east Himalayan region in future.